2012
DOI: 10.1063/1.3687918
|View full text |Cite
|
Sign up to set email alerts
|

Bias-enhanced nucleation and growth processes for improving the electron field emission properties of diamond films

Abstract: The evolution of diamond films in bias-enhanced-nucleation (BEN) and bias-enhanced-growth (BEG) processes was systematically investigated. While the BEN process can efficiently form diamond nuclei on the Si substrates, BEG with large enough applied field (> –400 V) and for sufficiently long periods (>60 min) was needed to develop proper granular structure for the diamond films so as to enhance the electron field emission (EFE) properties of the films. For the films BEG under −400 V for 60 min (af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
3
28
0
1
Order By: Relevance
“…It is to be indicated that in CH 4 /H 2 plasma, the bias current required at least 7.5 min to reach a saturated value after the application of À400 V bias voltage. 26 The saturated bias current in the BEG period was proportional to the bias voltage applied [solid squares, Fig. 1(b)] and reached 270 mA/cm 2 for À200 V bias voltage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be indicated that in CH 4 /H 2 plasma, the bias current required at least 7.5 min to reach a saturated value after the application of À400 V bias voltage. 26 The saturated bias current in the BEG period was proportional to the bias voltage applied [solid squares, Fig. 1(b)] and reached 270 mA/cm 2 for À200 V bias voltage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Teng et al 26 reported the enhanced EFE behavior of bias-enhanced grown (BEG) nanocrystalline diamond (NCD) films using CH 4 CH 4 /H 2 plasma and the feasibility of bias enhanced growth of UNCD films using CH 4 /Ar plasma has not been reported yet.…”
Section: /Ar Plasma I Introductionmentioning
confidence: 98%
“…These curves reveal that the application of negative bias voltage is more effective in lowering the turnon field for inducing the EFE processes. However, the EFE properties of both the beg-NCD À300V and the beg-NCD þ200V films are still better than those attainable for beg-MCD, 15 which has a large E 0 value of 17.7 V/lm when grown under a À300 V bias voltage (closed hexagon symbol, Fig. 7(c)).…”
Section: A Characteristics Of Beg-ncd Filmsmentioning
confidence: 95%
“…13,14 The formation of sp 2 bonded graphitic phases at the grain boundaries, which create conduction channels for the electrons to get transported, accounts for the improved EFE properties. 15 In contrast, the application of a positive bias voltage enhances the rate of growth of the diamond films as well as growth of grains in the favored orientation. [16][17][18] However, the reports on the effect of positive and negative bias voltages on modifying granular structure of diamond films are controversial.…”
mentioning
confidence: 96%
“…К настоящему времени для их приготовле-ния используются в основном термическое разложение метана в электрическом поле методами " горячей ни-ти" [1], физическое осаждение из пара в микроволно-вой плазме [2][3][4] и развиваемый нами способ пиролиза метана в зазоре между двумя углеродными пластинами, между которыми создается разность электрических по-тенциалов [5][6][7].…”
Section: Introductionunclassified